MAKNA DENOTATIF DAN KONOTATIF EMPAT KUTIPAN MILIK SAGE PADA PERMAINAN VALORANT: KAJIAN SEMANTIK - Parji, Rahmelia Prastamawati; Prihandini, Asih (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
This research aims to analyze the words in the Sage’s quotes one of the characters in the Valorant game, which has denotative and connotative meaning. The meaning of denotative word is word that has an actual meaning as it is written in the dictionary. Whereas the meaning of connotative word is word that has a meaning according to suggestion, or what is associated with a word that goes beyond its formal definition. Connotations are personal associations produced by words. Denotation is an objective relationship between the linguistic form and to which it refers. An example in one of the quotes is "You were a boulder. I'm a mountain." If denotatively interpreted, boulder is a big stone and mountain is a mountain. But if interpreted connotatively in Sage quotes, boulder and mountain are words that describe differences in size (strength). This research uses qualitative descriptive method, which is to gain a deeper understanding of individual participants, including opinions, perspectives, and attitudes. Data of this research taken from four Sage’s quotes uttered in the game Of Valorant. The four quotes spoken by Sage has connotative meanings with one of the reasons being to describe Sage's role as someone who has advantages over other characters. The connotative meaning contained in Sage's quote is more dominant than the denotative meaning. Keywords: Denotative and Connotative, Semantic, Quotes, Game